Does "Good Government" Draw Foreign Capital? Explaining China's Exceptional Foreign Direct Investment Inflow - Fan, Joseph P. H.; Morck, Randall; Xu, Lixin Colin; Yeung, Bernard (World Bank, Washington, DC, 2012)
China is now the world's largest destination of foreign direct investment (FDI), despite assessments highlighting its institutional deficiencies. But this FDI inflow corresponds closely to predicted FDI flows into China from a model that predicts FDI inflow based on government quality indicators and controls and is estimated across a sample of other weak-institution countries. The only real discrepancy is that, if government quality is measured by constraints on executive power, China receives somewhat more FDI than the model predicts. This might reflect an underestimation of the strength of these constraints in China, a unique institutional setting for FDI operations, FDI based on expected future institutional improvements, or a unique Chinese model of development. The authors conclude that Ockham's razor disfavors the last. They also note that FDI may be elevated because Chinese institutions protect foreign firms better than domestic ones.